A hybrid method for the solution of a sparse power system matrices on vector computers - Padilha, Antonio [UNESP]; Basso, Alessandro Ruiz [UNESP] (I E E E, 1996)
This paper describes a methodology for solving a linear system of equations on vector computer. The methodology combines direct and inverse factors. The decomposition and implementation of the direct solution in a CRAY Y-MPZE/232, and the performance results are discussed.